History in the era of abundance: web archives and historical research (2020)
Can the 1990s be considered the history of the present? As historians turn to study this period and beyond, they will encounter a historical record that is radically different from what has ever existed before. Old websites, social media, blogs, photographs, and videos are all part of the massive quantities of digital information that technologists, librarians, archivists, and organizations such as the Internet Archivehave been collecting for the past three decades.  This article explores how this dramatic shift in our historical record changes the work of historians. It does so in two main ways. First, it outlines the approaches, methods, tools, and search functions that can help a historian turn web documents into historical sources. Secondly, it considers the implications of the size and scale of digital sources, which amount to more information than historians have ever had at their fingertips, and much of which are by and about people who have traditionally been absent from the historical record.As a way to make these points tangible, it does so primarily through an in-depth case study of working with the GeoCities. com web archive, a collection of hundreds of millions of 1990s webpages.